Electronic Data Processing From the Management Viewpoint - Schmidt, Richard N. (Academy of Management Journal, 1958)
Provides information on electronic data processing from the company-wide management viewpoint. Views of executives about electronic data processing; Types of computers; Difference between the computer built for scientific research and the computer used for processing business data; Types of service provided by a data processing center; Example of how electronic data processing works; Steps in preparing for a computer operation.